0
$\begingroup$

Find an elementary matrix E such that AE = B

$$A = \begin{bmatrix} 2 & 4 \\ 1 & 6 \end{bmatrix}$$

$$B = \begin{bmatrix} 2 & -2 \\ 1 & 3 \end{bmatrix}$$

$$\begin{bmatrix} 2 & 4 \\ 1 & 6 \end{bmatrix}*E=\begin{bmatrix} 2 & -2 \\ 1 & 3 \end{bmatrix}$$

There should only be 1 elementary row operation performed on A. Scaling either row or swapping either row would not result in B, but I am unsure how to solve the specific pivot row operation that is used to obtain B.

$\endgroup$
  • 2
    $\begingroup$ The only matrix $C$ such that $AC=B$ would be $C=A^{-1}B$, whether $C$ happened to be an elementary matrix or not. $\endgroup$ – JMoravitz Feb 19 '18 at 3:59
  • $\begingroup$ Yes, I have the textbook answer (1 -3, 0 1) $\endgroup$ – mathguy Feb 19 '18 at 3:59
  • $\begingroup$ @JMoravitz that method would not work for CA = B right? $\endgroup$ – mathguy Feb 19 '18 at 4:21
  • 1
    $\begingroup$ If $CA=B$ then by right multiplication by $A^{-1}$ you get $C=BA^{-1}$. $\endgroup$ – JMoravitz Feb 19 '18 at 4:46
5
$\begingroup$

Hint:

Since the matrix $E$ appears on the right of matrix $A$, think of elementary column operation.

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

Hint:

Normally, one would use $E=A^{-1}B$ where $A^{-1}$ is the inverse of matrix $A$. Alternatively, we may let $$ E=\begin{bmatrix} a & b \\ c & d \end{bmatrix} $$ Hence one would have \begin{align} \begin{bmatrix} 2a+4c & 2b+4d \\ a+6c & b+6d \end{bmatrix}=\begin{bmatrix} 2 & -2 \\ 1 & 3 \end{bmatrix} \end{align} There rest should be easy peasy.

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

Think of getting $B$ from $A$ (it is a column operation): $$A=\begin{bmatrix}2 & 4 \\ 1 & 6 \end{bmatrix} \stackrel{-3\cdot C1+C2\to C2}{\Rightarrow} \begin{bmatrix}2 & -2 \\ 1 & 3 \end{bmatrix}=B.$$ Now do the same column operation with unit matrix: $$I=\begin{bmatrix}1 & 0 \\ 0 & 1 \end{bmatrix} \stackrel{-3\cdot C1+C2\to C2}{\Rightarrow} \begin{bmatrix}1 & -3 \\ 0 & 1 \end{bmatrix}=E.$$ Verify: $$AE=\begin{bmatrix}2 & 4 \\ 1 & 6 \end{bmatrix}\cdot \begin{bmatrix}1 & -3 \\ 0 & 1 \end{bmatrix}=\begin{bmatrix}2 & -2 \\ 1 & 3 \end{bmatrix}=B.$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.